Edible bird's nest improves motor behavior and protects dopaminergic neuron against oxidative and nitrosative stress in Parkinson's disease mouse model. (September 2018) - Yew, Mei Yeng; Koh, Rhun Yian; Chye, Soi Moi; Othman, Iekhsan; Soga, Tomoko; Parhar, Ishwar; Ng, Khuen Yen
Graphical abstract: Highlights: Sub-chronic treatment of EBN has no observable toxic effect on mice. EBN improves motor function, locomotor activity and balancing in PD mice. EBN prevents loss of dopaminergic neurons in substantia nigra of PD mice. Antioxidant and microglia markers are regulated by EBN in substantia nigra of PD mice. NO production and lipid peroxidation are attenuated by EBN in in vitro PD model. Abstract: Parkinson's disease (PD) is a neurological disorder originated from the death of dopaminergic neurons in the midbrain. Evidences showed that oxidative and nitrosative stress play a central role in neurodegeneration. In this study, we examine the neuroprotective effects of EBN (20 mg/kg and 100 mg/kg) in 6-hydroxydopamine (6-OHDA)-treated C57BL/6J mice. Twenty eight days of EBN oral administration greatly improved locomotor activity of PD mice in terms of travel distance and balancing. EBN also protected dopaminergic neuron against 6-OHDA in the substantia nigra. EBN reversed the reduction in the expression of antioxidant enzyme glutathione peroxidase 1 and the increased microglia activation in PD mice. Our results also showed that EBN effectively reduced 6-OHDA-induced nitric oxide formation and lipid peroxidation in SH-SY5Y cells. The data altogether indicates that EBN exerted neuroprotection through enhancement of antioxidant enzyme activity and the inhibition of microglia activation, nitric oxide formation and lipid peroxidation in PD model.